Enzymatic hydrolysis of oil palm empty fruit bunch using immobilized cellulase enzyme - Al-Khatib, Ma'an Fahmi Rashid; Mohammed Abd, Rasha; Alam, Md Zahangir; Mohd. Salleh, Hamzah (Academic Journals, 2011)
The rapid development and the economic growth of oil palm industry have exacerbated environmental pollution since it results in large quantity of waste products produced from the oil extraction process. In many cases, however, low catalytic efficiency and instability of enzymes were considered as barriers for the development of large-scale operations and applications. In this study, hydrolysis of oil palm empty fruit bunch to reducing sugar was achieved using cellulase enzyme immobilized on multi-wall carbon nanotubes. The hydrolysis evaluation was performed using free cellulase enzyme. The amount of reducing sugar concentration released during the reaction was determined using dinitrosalicylic acid(DNS) assay. Using the immobilized form of the enzyme, it was found that the reducing sugar concentration was increased and the enzymatic hydrolysis of oil palm empty fruit bunch was enhanced greatly over long time of hydrolysis.